2010
DOI: 10.1007/s11695-010-0303-z
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery is Associated with Reduced Depressive Symptoms and Better Sexual Function in Obese Female Patients: A One-Year Follow-Up Study

Abstract: Bariatric surgery is an effective treatment for obesity; few studies, however, have investigated its impact on patients' sexuality. We aimed to determine bariatric surgery's effect on female patients' body mass index (BMI), anxiety and depressive symptoms, and sexual function and delineate predictors of treatment outcomes. Fifty-nine obese female bariatric candidates were administered the Hospital Anxiety and Depression Scale and the Female Sexual Function Index 1 week before surgery (T1) and 1 year after (T2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 18 publications
4
55
0
6
Order By: Relevance
“…On the contrary, other studies reveal no significant changes in anxiety measurements postoperatively 48,49,56 .…”
Section: Mood Disordersmentioning
confidence: 78%
See 1 more Smart Citation
“…On the contrary, other studies reveal no significant changes in anxiety measurements postoperatively 48,49,56 .…”
Section: Mood Disordersmentioning
confidence: 78%
“…The majority of studies have reported a decrease in depression and depressive symptoms after bariatric surgery 24,27,[48][49][50][51][52][53][54][55][56] . Women seem to show a more marked decline than men 57 .…”
Section: Mood Disordersmentioning
confidence: 99%
“…10 Noutros casos, verificaram-se melhorias em termos de patologia depressiva ou ansiosa, com melhores resultados para a depressão. 12,18,19,23 A diabetes mellitus tipo 2 e as perturbações do foro psicológico/psiquiátrico são problemas que ocorrem em simultâneo e que se poderão relacionar entre si, sendo importante compreender a sua evolução após realização de cirurgia bariátrica e a sua influência nos resultados da cirurgia. 12,24,25 Tem sido demonstrado que tanto o comportamento alimentar 14,22 como a depressão 9,13 no período pós--cirúrgico se associam a uma menor perda de peso.…”
Section: 17unclassified
“…12,18,19,23 Contudo, esta é uma área de conhecimento que necessita de maior investigação porque estes resultados não são consistentes entre os diferentes estudos.…”
unclassified
“…Siden Kremen og kolleger publiserte sin første studie om fedmekirurgi på begynnelsen av 1950-tallet, har også forskningsinteressen knyttet til denne behandlingen vokst betraktelig. Saerlig finnes mye dokumentasjon av de målbare effektene av fedmekirurgi i form av vekttap, bedring i livskvalitet, bedring av diabetes, samt bedring av psykososial fungering (4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Innledningunclassified